Perceptions of Communications Mix as a Bank Marketing Strategy- The Case of Rural and Community Banks In Ghana (Global Journal of Human-Social Science, 2020)
The study aimed to explore and find out the perceptions of staff and customers on communication mix strategies employed by the selected banks A multi-stage sampling technique was used in selecting the final 561 samples for the study 1 The quota sampling technique was used in the first stage 2 The simple random sampling technique was used in the second stage to select the representative RCBs from each of the ten 10 regions Lastly purposive sampling and simple random sampling techniques were used to select the manager of marketing and communications as well as employees and clients from each of selected RCBs from the ten regions respectively in the third stage Findings from the study revealed that there is a positive perception of marketing communication importance among the selected Rural Banks in Ghana The overall perception index of 0 50 further suggests that clients of RCBs across the country have a positive perception about the operation of the RCBs in Ghana and their choice of the marketing communication mix Additionally clients and staff of the RCBs had a relatively good perception of communications mix employed by the RCBs and agreed to the extent that marketing communications arecritical to the survival of RCBs
Keywords: marketing communication; perception; strategy; ghana